Prevention of Respiratory Distress After Laparoscopic Cholecystectomy - O. A. Dolina; V. V. Valetova (Общая реаниматология)
The paper presents the results of a comparative study of different methods for preventing respiratory distress after laparoscopic cholecystectomy. It shows the advantages of use of noninvasive assisted ventilation that ensures excessive positive pressure in the respiratory contour, its impact on external respiratory function, arterial blood gases, oxygen transport and uptake. A scheme for the prevention of respiratory diseases applying noninvasive assisted ventilation is given.